Recombinant production and activity assessment of growth stimulatory proteins in the resuscitation of mycobacterium tuberculosis - Campbell, Lisa (My University, 2020)
Mycobacterium tuberculosis (Mtb) is able to enter a non-culturable, dormant-like, state under stressful conditions to evade eradication. When growth permissive conditions resume, Mtb can exit this non-culturable state and resume active replication. Non-culturable populations are of great interest in clinical settings as they can contribute to misdiagnoses and inaccurate treatment monitoring. Resuscitation promoting factors (Rpfs) have been implicated as stimulatory growth factors for resuscitation from the non-culturable state, together with their interacting partner, Rpf-interacting protein A (RipA). In this study the resuscitation capabilities of Resuscitation promoting factor B (RpfB) and RipA against Mtb were evaluated. The catalytic regions of RipA and RpfB were expressed and purified and their muralytic activity was assesed using four protein activity assays. The resuscitation capabilities of RipA and RpfB in Mycobacterial growth indicator tube (MGIT) assays was evaluated using carbon starvation-derived non-culturable Mtb from the laboratory strain (H37Rv). It was observed that RipA and RpfB supplementation was able to stimulate the resuscitation of non-culturable, carbon-starved H37Rv, significantly decreasing its time-topositivity (TTP) in MGIT assays compared to un-supplemented MGIT media. Upon investigating clinical strains of Mtb, no significant reduction in TTP of non-culturable, carbon-starved Beijing and LAM isolates was reported. Supplementation of RipA and RpfB in MGIT assays to improve the detection of clinical isolates of Mtb and enhance their TTP was evaluated using a South African cohort of 30 sputum specimens. Overall RipA and RpfB supplementation yielded no significant improvements to MGIT TTP, regardless of initial colony forming units, patient gender, immunology or diagnostic data; however, 20% of individual specimens did benefit from the supplementation, yielding improved TTP when compared to un-supplemented MGITs. No significant adverse effects were observed during supplementation and given the positive yield in some specimens, it is suggested that the addition of RipA and RpfB could improve the detection of Mtb in clinical specimens.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020